New remains of Elephantidae from the Upper Siwalik subgroup (Plio-Pleistocene) of Pakistan. (15th November 2019) - Abbas, Sayyed Ghyour; Khan, Muhammad Akbar; Babar, Muhammad Adeeb; Akhtar, Muhammad
Abstract: The Siwalik sequence saw the appearance and spread of the family Elephantidae in the Indian subcontinent during the Plio-Pleistocene epochs. Elephas flourished and underwent species turnover during the Plio-Pleistocene of the Siwalik Group. The newly discovered specimens include serially arranged M2-3 and partial maxillary fragment with M2 of Elephas planifrons, and M3 and partial dp4 of Elephas hysudricus from the Pinjor Formation (Pleistocene) of the Siwaliks. A tusk from the Tatrot Formation (Pliocene) of the Siwaliks, has been assigned to Elephantoidea indet. Based on the comparison with the stratigraphically well-dated mammalian fauna from the various Siwalik localities of the Indian subcontinent, the age of Sardhok, Panjan Sher Shahana and Kurla Sharif range is suggested to be from the Late Pliocene (Piacenzian) to Late Early Pleistocene (Calabrian), and a savannah like environment is suggested for these localities. Highlights: The article mainly deals with the remains Elephas planifrons and E. hysudricus from the Pakistan Siwalik after a long gap and their diagnoses have been revised based on previous and recent data. The material described here is from well-known provenance as compared to most of the previously described material of these species. The described M2 Elephas planifrons and M3 of E. hysudricus adds more data to the morphometric characters. Correlation between the various Pakistani and Indian areas yielding Late Pliocene to Early Pleistocene fauna has been attempted. A savannah like environment is suggested for the studied areas based on the recovered fauna. Reported the Elephas planifrons and E. hysudricus remains from the Pakistan Siwaliks with their revised diagnoses.